Central Obesity and Associated Factors among Adult Patients on Antiretroviral Therapy (ART) in Armed Force Comprehensive and Specialized Hospital, Addis Ababa, Ethiopia - Adnan Kemal; Mohammed Ahmed; Melese Sinaga Teshome; Kalkidan Hassen Abate (Journal of Obesity)
Background. Similar to the general population, the prevalence of central obesity is increasing among HIV-infected persons. There are little data on the burden of abdominal obesity using the waist-to-hip ratio measurement in HIV-infected patients in resource-limited settings, including Ethiopia. Therefore, this study aimed to assess the prevalence and associated factors of central obesity among HIV patients taking ART in an armed force comprehensive and specialized hospital, Addis Ababa, Ethiopia. Methods. A cross-sectional study was conducted from March to April 2018. A systematic sampling method was used to select 353 study participants. Pretested World Health Organization stepwise questionnaire, document review, and anthropometric and biochemical measurements were used to collect data on different variables under the study. The collected data were entered into EpiData version 3 and analyzed by SPSS version 21. An adjusted odds ratio with 95% CI was considered to declare a statistically significant association. Results. The prevalence of central obesity in this study was 71.7% (95% CI: 67%–76.4%). Besides, the odds of central obesity were associated with being female (AOR: 85.6; 95% CI: 20.09, 364.6), among merchants (AOR: 18.8; 95% CI: 1.39, 255.7), CD4 count <200 cells/mm3 (AOR: 0.03; 95% CI: 0.007, 0.160), among respondents taking AZT + 3TC + EFV-based ART regimen (AOR: 8.73; 95% CI: 1.33, 57.17), ABC + 3TC + ATV/r-based regimen (AOR: 0.18; 95% CI: 0.03, 0.94), increased BMI (AOR: 3.50; 95% CI: 1.36, 3.89), and abnormal blood pressure (AOR: 2.53; 95%: 1.13, 5.67). Conclusion. It is possible to conclude that central obesity is a huge public health problem among the HIV-infected population in the study area. Being female, increased BMI, low CD4 count, AZT + 3TC + EFV, ABC + 3TC + ATV/r-based regimen, and abnormal blood pressure were associated with central obesity. Therefore, adequate attention must be paid to primary and secondary control of these factors to reduce the prevalence of abdominal obesity among HIV-infected patients.